PHOTOOPHTHALMOLOGY WITHOUT REFLECTIONS - RIVAS CHERIF, MANUEL DE (Universidad S, Departamento Agricultura, CD MEXICO, DF, MEX, 1941)
An apparatus is described and illustrated, and optical considerations are discussed Reflections in the photographic image cannot be eliminated in apparatus with a single objective, but are eliminated by the author's apparatus
CIENC MEX
Keywords: PHOTOOPHTHALMOLOGY, REFLECTIONS; CIENCIAS MEDICAS; CIENCIAS CLINICAS; OFTALMOLOGIA